Periodically collapsing rational bubbles in exchange rate: A Markov-switching analysis for a sample of industrialised markets - José Eduardo de A. Ferreira (University of Kent, Department of Economics, 2006)
This paper investigates the presence of periodically collapsing rational bubbles in exchange rates for a sample of industrialised countries. A periodically collapsing rational bubble is defined as an explosive deviation from economic fundamentals with distinct expansion and contraction phases in finite time. By using Markov-switching regime models we were not able to find robust evidence of a bubble driving the exchange rate away from fundamentals. Moreover, the results also revealed significant non-linearities and different regimes. The importance of these findings suggests that linear monetary models may not be appropriate to examine exchange rate movements.
Keywords: F31; F37; F41; 330; Foreign Exchange; Bubbles; Fundamentals; Markov-Switching; Assets